2023
DOI: 10.1186/s13023-023-02788-1
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary abscess: a case report and systematic review of 488 cases

Abstract: Background Pituitary abscess (PA) is a rare condition and not well understood. We aimed to describe a case and perform a comprehensive systematic review to explore presenting symptoms, radiological findings, endocrine abnormalities and mortality. Aim To identify presenting symptoms, radiological findings, endocrinological abnormalities and predictors of mortality for PA. Methods We systematically revie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 193 publications
0
5
0
Order By: Relevance
“…Prior reports have demonstrated that up to 50% of pituitary abscesses yielded negative culture results, indicating the presence of a sterile abscess. 1 9 Interestingly, a previous study found a differential rate of sterile abscesses in primary versus secondary abscesses with rates of 15% versus 35%, respectively. 8 Some surgeons attribute the high frequency of sterile abscesses to the view that those abscesses may not be abscesses at all; rather, sites of aseptic, liquefactive necrosis due to a previously infarcted pituitary gland or tumor.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Prior reports have demonstrated that up to 50% of pituitary abscesses yielded negative culture results, indicating the presence of a sterile abscess. 1 9 Interestingly, a previous study found a differential rate of sterile abscesses in primary versus secondary abscesses with rates of 15% versus 35%, respectively. 8 Some surgeons attribute the high frequency of sterile abscesses to the view that those abscesses may not be abscesses at all; rather, sites of aseptic, liquefactive necrosis due to a previously infarcted pituitary gland or tumor.…”
Section: Discussionmentioning
confidence: 97%
“…In the majority of reports, headache is the most common presenting symptom of pituitary abscess with the most recent review demonstrating a frequency of 76.2%. 1 Despite being the most common symptom, however, the location of reported headaches can be variable, including bifrontal, retroorbital, and vertex headaches. 9 Due to the lack of a characteristic pattern, presence of a headache may not be a helpful tool for diagnosis of a pituitary abscess, and both clinical features, as well as laboratory results reflective of pituitary hypofunction, may be more useful to aid in diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The structure in question is situated in a deep region of the brain, resulting in a somewhat secluded position that offers protection against typical sources of infection. This is in contrast to the pituitary gland, which is more exposed and hence more prone to infections 3 , 4 . Pineal infections can still occur infrequently in this area for a variety of causes, such as direct extension from adjacent tissues or hematogenous dissemination.…”
Section: Possible Pathophysiologic Factors Diagnosis and Treatmentmentioning
confidence: 91%